The Development of Data Collection Tools to Measure Parent–Infant Closeness and Family‐Centered Care in NICUs. Issue 6 (19th November 2020) - Axelin, Anna; Raiskila, Simo; Lehtonen, Liisa
Abstract: Background: Preterm and sick infants benefit from parent–infant closeness and family‐centered care (FCC) in neonatal intensive care units (NICUs). Prospective and feasible tools are needed to measure these care practices to facilitate their implementation. Aims: To describe the development process of three prospective data collection tools that measure parent–infant closeness and the quality of FCC. Methods: Data collection tools were developed in an iterative process consisting of three development cycles. Feedback was gathered from parents, staff, and researchers. The first stages of development focused on the content validity, appropriate scaling, and optimization of the response rate of these tools. Results: The study included parents of 490 infants and the nurses working at bedside in 15 NICUs in six countries. The Parent‐Infant Closeness Diary was developed to measure the daily duration of parental presence, holding, and skin‐to‐skin contact. The optimal duration for daily diaries was 14 consecutive days to maintain a good response rate. Parents provided reliable documentation of parent–infant closeness. Digital FCC tools covering the nine aspects of FCC for parents and nurses were developed to measure the quality of FCC. Participants provided answers on a 7‐point Likert scale. Parents' response rates remained >50% for approximately 1 month, and the nurses' mean response rate was 55% (39%–87%) for the 3‐month study period. Linking Evidence to Action: These new tools provide prospective daily information to aid the implementation of parent–infant closeness and the quality of FCC in NICU in different countries. They can be used to study and evaluate the implementation of these clinical practices NICUs in an international context.